The Fund's Mandate : The Future Financing Role. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper examines the implications of the Fund accepting membership in the Financial Stability Board ('FSB'). The FSB Charter (the ?Charter?) explicitly contemplates the possibility of the Fund and the other international financial institutions becoming members but notes that ?the acceptance of membership by the international financial institutions (IFIs) in the FSB is subject to the approval of their respective governing bodies.? An Executive Board decision is required for the Fund to accept membership and is proposed below.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet